SEMIOSIS PROCESS IN THE SOUNDS OF GAMELAN AND PESINDEN IN SANDEKALA FILM - Pratama, Andri Albertha; Soewarlan, Santosa (Seni Media Rekam ISI Surakarta, 2019)
The research investigates the use of the sign (code) used by Amriy Ramadhan as the director when delivering messages through the sounds of ‘gamelan’ and ‘pesinden’ in the Sandekala film. Conflicts emerged when the signs that are used have broad interpretations for the audience. The signs are discribed and analyzed using the ten-sign classification analysis method from the Peirce semiotic trichotomy concept. This study shows the important meaning of the semiosis process of the distribution of other signs which in their presentation are interrelated to lead the audience's interpretation in the sounds of ‘gamelan’ and ‘pesinden’ presented in the Sandekala film. The using signs which the characteristic based are generally accepted convention such as non-verbal dialect (kinesics) can lead the audience's interpretation that the sound of ‘gamelan’ and ‘pesinden’ in the Sandekala film is a metonym of magical figure who has long hair, white dress based on the semiosis process of signs which are interrelated in the presentation of the narrative structure of the film with repeated indexical relationship patterns.